Simulating the impact of Grain-for-Green Programme on ecosystem services trade-offs in Northwestern Yunnan, China - Peng, Jian; Hu, Xiaoxu; Wang, Xiaoyu; Meersmans, Jeroen; Liu, Yanxu; Qiu, Sijing (Elsevier, 2019)
Prefecture in 2000, land use/cover has undergone dramatic changes. This study used the CLUE-S model to simulate land use change in 2030, and explored the spatial pattern and relationship of different ecosystem services under the four scenarios of GFGP. The results show that, GFGP can help to improve indirect services of ecosystems, such as carbon storage and soil conservation. However, direct services of the ecosystem will decline, such as food production and water yield. Compared with 2010, the overall supply level of the four ecosystem services is the most balanced in the moderate GFGP scenario. In this scenario, total food production decreased by 179,000 tons and water yield decreased by 57 million cubic meters. Carbon storage and soil conservation continued to grow, increasing by 21.86 million tons and 17.87 million tons, respectively. The changes of ecosystem services in the strong GFGP scenario are extreme. The increases in carbon storage and soil conservation are at the expense of a significant reduction in food production and water yield. It can be concluded that GFGP may lead to intensifying ecosystem services trade-offs. Through comparing the changes of ecosystem services under different GFGP scenarios, it is found that the implementation intensity of GFGP should be deeply concerned in policy making.
Keywords: Grain-for-Green Programme; Ecosystem services trade-offs; Scenario analysis; Northwestern Yunnan